Understanding Multidimensionality of Muslim Women's Experiences of Sexual Violence Through the News Coverage of the Bilkis Banu Gang Rape Case in India. (2nd January 2023) - Fadnis, Deepa
ABSTRACT: Research suggests that the media in India determines the newsworthiness of a rape case based on the social and demographic identifiers of the victim. Bilkis Banu's gang rape case was one of the few cases covered by the media where the victim belonged to a minority community. Banu, a young Muslim woman was gang raped in 2002 by a mob of hardline Hindu men, as she was fleeing her riot-torn village in Gujarat. Using the intersectional lens, this paper analyzes the news discourse in the Bilkis Banu gang rape case as covered by the Times of India over a period of 17 years. It endeavors to understand the impact of politicized religion in the construction of Muslim women's intersectional identity as victims of sexual assault in the media. The dominant narratives within this news discourse suggest that Banu's experience as a victim of sexual violence is intentionally ignored on account of her religious identity. Additionally, in-depth interviews with journalists at English-language publications in India discuss issues related to access and stigma that are linked to the victim's social status.